Comparative Study of the Effect of Interocclusal Recording Materials on Reproducibility of Horizontal Condylar Registrations in Arcon and Non – Arcon Articulators: A Clinical Study - Neupane, G; Sapkota , B; Basynet, S KC; Rimal, U; Mahanta , S K (Journal of Nepalese Prosthodontic Society, 2024)
Introduction: Horizontal condylar inclination is the mechanical equivalent of condylar guidance. Different techniques to record horizontal condylar inclination are interocclusal recording materials, radiographic interpretation, extraoral recording devices. The objective of the study was to evaluate the effects of three different interocclusal recording materials on reproducibility of horizontal condylar inclination in two different semi-adjustable articulators (arcon and non-arcon) and compare with the values obtained from lateral cephalogram.Methodology: The studied group consisted of patients with age group 20-35 years. Single protrusive record for each of three different recording materials were made with the help of custom-made protrusive guide for each volunteer. These records were used for programming two articulators for both right and left sides three times and the respective HCI values were noted. The resultant valuesfor both the articulators and values of right side were compared with values obtained from tracing of lateral cephalogram. The results obtained were tabulated and subjected to statistical analysis.Results: The difference in means of right and left HCI and individual values for all interocclusal recording materials in both articulators were statistically insignificant. HCI values obtained clinically with 3 different interocclusal recording materials in two different semiadjustable articulators (Right side only) compared with that obtained from lateral cephalograms was found to be statistically significant.Conclusion: The results indicate that no statistically significant difference in inclination of the condylar path between right and left side with 3 different interocclusal recording material using arcon and nonarcon articulators. The lateral cephalograms showed the higher horizontal condylar inclination values than the clinical methods.